Aplikasi Moblie Learning untuk Meningkatkan Interaksi Pembelajaran dalam Mendukung Penyerapan Materi Pembinaan UMKM oleh LPPM Universitas Kristen Petra dengan Menerapkan Model Learning Group - Cynthia Wijaya; Djoni Haryadi Setiabudi; Justinus Andjarwirawan (Universitas Kristen Petra, 2022)
Synchronous learning provided by LPPM in learning events is often limited, and makes MSME participants have to understand and develop the material that has been delivered individually after receiving the lesson. This makes the lack of interaction in learning, and reduces the interest and attention of MSMEs to improve learning from the material obtained, especially when they find difficulties in learning. This can affect the level of absorption of material by MSMEs to be not optimal. Several previous studies using mobile learning still have weaknesses, namely learning is still more focused on individual learning so there is no interaction in the learning process through mobile learning.To overcome this problem, in this study a mobile learning application was designed with a learning group model that has collaborative features, such as the task forum feature where MSMEs can choose the question to be worked on and then give each other comments on whether the answers in each question are correct, problem box to help each other provide solutions from a lack of understanding of the material, discussion forums to discuss things that have not been discussed in the material, glossary, chat with tutors and mobile push notification support to encourage MSMEs to be more active in mobile learning.The results of this study based on questionnaires and activity calculations, it can be concluded that the mobile learning application with the learning group model helps MSMEs to understand or increase the absorption of material in training. In addition, it also makes MSMEs active in participating in the training, thus indirectly helping better absorption of material.